Neoadjuvant (re)chemoradiation for locally recurrent rectal cancer: Impact of anatomical site of pelvic recurrence on long-term results. (December 2020) - Sorrentino, Luca; Belli, Filiberto; Valvo, Francesca; Villa, Sergio; Guaglio, Marcello; Scaramuzza, Davide; Gronchi, Alessandro; Di Bartolomeo, Maria; Cosimelli, Maurizio
Abstract: Background: Selection criteria to propose neoadjuvant (re)chemoradiation (CHRT) in locally recurrent rectal cancer (LRRC) are required, since re-irradiation is sometimes associated to severe adverse effects. Aim of the present study was to compare chances of R0 surgery and disease-free survival (DFS) in LRRC patients (pts) treated by neoadjuvant (re)CHRT followed by surgery vs. upfront surgery, stratifying pts by each localization of LRRC. Methods: LRRC pts treated at the National Cancer Institute of Milan (Italy) were retrospectively divided into two groups: neoadjuvant (re)CHRT vs. upfront surgery. According to our Milan classification, LRRC were categorized as S1, if located centrally (S1a-b) or anteriorly (S1c) within the pelvis; S2, in case of sacral involvement; S3, in case of lateral pelvic wall infiltration. Results: 152 pts were candidate for multimodal treatment: 49 (32.2%) by neoadjuvant (re)CHRT and surgery, including 33 re-irradiations, vs. 103 (67.8%) by upfront surgery. No difference was observed in R0 resection rates (respectively 47.6% vs. 51.0%). However, neoadjuvant (re)CHRT followed by surgery improved the DFS (p = 0.028), also in R1 procedures (p = 0.013), compared with upfront surgery. At multivariate analysis, the R+ surgery (p < 0.0001) strongly predicted unfavorable DFS, while neoadjuvant (re)CHRT followed by surgery was independently associated to better DFS (p = 0.0197). Stratifying by LRRC localization, the combined approach significantly improved DFS in the S1c (p = 0.029) and S2 (p = 0.004) subgroups compared to upfront surgery, but not in S1a-b and S3 pts. Conclusion: Anterior (S1c) and sacral-invasive (S2) pelvic recurrences significantly benefit in terms of DFS by combination of neoadjuvant (re)CHRT and radical surgery, also after R1 resection. Highlights: Role of neoadjuvant re-chemoradiation in locally recurrent rectal cancer is unclear. No difference was observed in R0 resection rates. Neoadjuvant re-chemoradiation improved the DFS, also in R1 surgery. Disease-free survival was increased mainly in anterior and sacral-invasive relapses.